Community-level impacts of low-level diesel exposure on a natural cold-temperate/subarctic phytoplankton assemblage - Andreana M. Cadaillon; Irene R. Schloss; O. Magalí Olmedo-Masat; Michel Starr; Francesca Vidussi; Behzad Mostajir; Daniel Pech; Gustavo Ferreyra (Marine Pollution Bulletin, 2026)

Variability of Dissolved Inorganic Carbon in the Most Extensive Karst Estuarine-Lagoon System of the Southern Gulf of Mexico - José Andrés Martínez-Trejo; José Gilberto Cardoso-Mohedano; Joan-Albert Sanchez-Cabeza; José Martin Hernández Ayón; Ana Carolina Ruiz-Fernández; Mario Alejandro Gómez-Ponce; Linda Barranco; Daniel Pech (Estuaries and Coasts, 2024)
Coastal ecosystems with karstic geology have a unique characteristic where the dissolution of carbonate rocks can increase total alkalinity (TA) and dissolved inorganic carbon (DIC). This results in higher inorganic carbon budgets in coastal areas. One such ecosystem is the Terminos Lagoon, the most extensive tropical estuarine lagoon system in Mexico, located in the karstic aquifer of the Yucatan Peninsula and connected to the southern Gulf of Mexico (sGoM). We measured TA and DIC to evaluate the variability in Terminos Lagoon’s of the carbonate system. We also estimated pH, partial CO 2 pressure (pCO 2 ), and aragonite saturation (Ω Ar ) along two transects from the main lagoon tributaries (Palizada and Candelaria rivers) to the coastal zone during the dry and rainy seasons. During the dry season, TA and DIC concentrations were significantly higher (3092 ± 452 µmol kg -1 TA, 2943 ± 522 µmol kg -1 DIC) than during the rainy season (2533 ± 228 µmol kg −1 TA, 2492 ± 259 DIC µmol kg −1 ). Our calculations indicate that the rainy season pCO 2 (2532 ± 2371 µatm) seems higher than in the dry season (1534 ± 1192 µatm). This leads to a reduction in pH (7.9 ± 0.3 to 7.8 ± 0.3). These significant changes indicate that rain increases the flow of unsaturated river water into the lagoon. The results of this work contribute toward a dissolved inorganic carbon variability baseline in the sGoM and can be helpful to Terminos Lagoon decision-makers.

The absence of disturbances promoted Late Holocene expansion of silver fir (Abies alba) in the Bohemian Forest - Nick Schafstall; Helena Svitavská-Svobodová; Martin Kadlec; Mariusz Gałka; Petr Kuneš; Přemysl Bobek; Viktor Goliáš; Pavel Pech; Daniel Nývlt; Pavel Hubený; Niina Kuosmanen; Vachel A. Carter; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Vertical variability in the diversity and abundance of fish larvae in a shallow tropical estuary in Southern Gulf of Mexico - Violeta Y. Coutiño-Sánchez; Manuel Mendoza-Carranza; Wendi Arévalo-Frías; Daniel Pech (Regional Studies in Marine Science, 2023)

Cryptic Diversity in Sympatric Migonemyia migonei (Diptera: Psychodidae), Eventual Meaning for Leishmaniasis Transmission - Sofía Lorián Moya; Angélica Pech-May; María Gabriela Quintana; Oscar Daniel Salomón (Neotropical Entomology, 2023)

Free-living nematode assemblages along a water-depth gradient in the Perdido belt, northwestern Gulf of Mexico - Abel Abraham Vargas-Espositos; Alberto de Jesús-Navarrete; Wilbert Andrés Pérez-Pech; Daniel Pech; Axayacatl Rocha-Olivares; Ivonne Martínez-Mendoza (Regional Studies in Marine Science, 2023)

Diel variation of the epibenthic community associated with seagrasses in a subtropical biosphere reserve - José Ángel García-Trasviña; Daniel Pech; Mariana E. Callejas Jiménez; Alberto De Jesus-Navarrete (Estuarine, Coastal and Shelf Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of a Light Crude Oil Spill on a Tropical Coastal Phytoplankton Community - Sébastien Putzeys; Miryam Juárez-Fonseca; Sonia S. Valencia-Agami; Armando Mendoza-Flores; Daniel Cerqueda-García; Ana C. Aguilar-Trujillo; Manuel E. Martínez-Cruz; Yuri B. Okolodkov; Flor Arcega-Cabrera; Jorge A. Herrera-Silveira; M. Leopoldina Aguirre-Macedo; Daniel Pech (Bulletin of Environmental Contamination and Toxicology, 2022)

Spatial Trends of the Potential Association Between Benthic Macrofauna and non-Source Point Sediment Pollutants in the Yucatán Continental Shelf - Daniel Pech; Flor Arcega-Cabrera; Ivan Hernández-Avila; Carlos E. Paz-Ríos (Bulletin of Environmental Contamination and Toxicology, 2022)

Biodiversity and biogeographic affinity of benthic amphipods from the Yucatan Shelf: an analysis across the warm Northwest Atlantic ecoregions - Carlos E. Paz-Ríos; Daniel Pech; Luis F. Carrera-Parra; Nuno Simões (Systematics and Biodiversity, 2021)

Species richness and spatial distribution of benthic amphipods (Crustacea: Peracarida) in the Alacranes Reef National Park, Gulf of Mexico - Carlos E. Paz-Ríos; Nuno Simões; Daniel Pech (Marine Biodiversity, 2019)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Two highly divergent alcohol dehydrogenases of melon exhibit fruit ripening-specific expression and distinct biochemical characteristics - Daniel Manríquez; Islam El-Sharkawy; Francisco B. Flores; Fikri El-Yahyaoui; Farid Regad; Mondher Bouzayen; Alain Latché; Jean-Claude Pech (Plant Molecular Biology, 2006)

Functional Characterization of a Melon Alcohol Acyl-transferase Gene Family Involved in the Biosynthesis of Ester Volatiles. Identification of the Crucial Role of a Threonine Residue for Enzyme Activity* - Islam El-Sharkawy; Daniel Manríquez; Francisco B. Flores; Farid Regad; Mondher Bouzayen; Alain Latché; Jean-Claude Pech (Plant Molecular Biology, 2005)